2000
DOI: 10.1523/jneurosci.20-14-05503.2000
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity and Firing Rate As Candidate Neural Codes for the Frequency of Vibrotactile Stimuli

Abstract: The flutter sensation is felt when mechanical vibrations between 5 and 50 Hz are applied to the skin. Neurons with rapidly adapting properties in the somatosensory system of primates are driven very effectively by periodic flutter stimuli; their evoked spike trains typically have a periodic structure with highly regular time differences between spikes. A long-standing conjecture is that, such periodic structure may underlie a subject's capacity to discriminate the frequencies of periodic vibrotactile stimuli a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
329
6
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(375 citation statements)
references
References 54 publications
38
329
6
2
Order By: Relevance
“…Perceptual decision-making both in the visual and somatosensory domains has emphasized the existence of at least two stages in stimulus processing leading to stimulus discrimination; mainly a bottom up process followed by higher-level involvement of areas responsible for perceptual decision-making Romo et al, 2003;Salinas et al, 2000). Our results confirm the existence of at least two stages leading to perceptual decision across sensory modalities.…”
Section: Comparison To Existing Literaturesupporting
confidence: 79%
See 1 more Smart Citation
“…Perceptual decision-making both in the visual and somatosensory domains has emphasized the existence of at least two stages in stimulus processing leading to stimulus discrimination; mainly a bottom up process followed by higher-level involvement of areas responsible for perceptual decision-making Romo et al, 2003;Salinas et al, 2000). Our results confirm the existence of at least two stages leading to perceptual decision across sensory modalities.…”
Section: Comparison To Existing Literaturesupporting
confidence: 79%
“…The idea is that even if the actual decision is made by higher-level cortices by integrating accumulated sensory evidence, stimulus identification can already be inferred from activity in low-level sensory areas. During a vibrotactile discrimination experiment, single-unit recordings in somatosensory cortex predicted whether monkeys could perceive a difference in the stimulation frequency (Salinas et al, 2000). In the same kind of tasks, Romo et al (Romo et al, 2003) demonstrated the role of medial prefrontal and premotor cortices in forming the decision initially driven by evidence in somatosensory areas (see also de Lafuente and Romo, 2005;Hernandez et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…At the moment, experimental data seem insufficient to determine this. Based on anatomical considerations (White, 1989;Braitenberg and Schüz, 1997) and neurophysiological measurements (Fetz et al, 1991;Nelson et al, 1992;Zohary et al, 1994;Salinas et al, 2000), it seems likely that all terms are different from zero, at least for local microcircuits; but what really needs to be known is the final weighted sum. This final sum might not be constant, neither in time nor across cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are at least three reasons why the effects of correlations on single cells should be fully characterized. First, correlations in spike counts have indeed been observed (Gawne and Richmond, 1993;Zohary et al, 1994;Salinas et al, 2000) and, based on the convergent connectivity of the cortex (White, 1989;Braitenberg and Schüz, 1997), they must be ubiquitous (Shadlen and Newsome, 1998;Bair et al, 1999). Second, such correlations may alter the coding capacity of a neuronal population (Gawne and Richmond, 1993;Zohary et al, 1994;Abbott and Dayan, 1999).…”
Section: Abstract: Random-walk; Integrate-and-fire; Computer Simulatmentioning
confidence: 99%
“…Studies on monkey tactile working memory showed that in the somatosensory system, activities of neurons in somatosensory cortex (primary and secondary, SI and SII) and the posterior parietal cortex (PPC) were correlated with performance of tactile-tactile unimodal working memory tasks (e.g., Koch and Fuster, 1989;Zhou and Fuster, 1996;Bodner et al, 1997;Salinas et al, 2000;Bodner et al, 2005). In those studies, the neural activity of tactile working memory was investigated through analysis of single-unit data recorded in awake monkeys performing delayed matching-to-sample tasks in which a tactile sample stimulus was first presented, and the animal had to memorize the sample throughout the delay period until the tactile matching test stimulus was presented for choice.…”
Section: Introductionmentioning
confidence: 99%